Formulation of sheet mask utilizing Pometia pinnata Fruit Peel Waste as Anti-Aging and Anti-Bacterial Agent in Facial Skin Carekin Care - Rizki Safarudin; M. Rafly Syahputra; Vivi Anggia; Isra Janatiningrum (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Pometia pinnata fruit peel extract contains secondary metabolites, such as tannins, saponins, and flavonoids, which demonstrate both antioxidant and antibacterial properties. Despite the potential identified in matoa fruit peel, its utilization remains constrained. Consequently, there is a necessity for innovative approaches to unlock its latent capabilities. Universal desires for skin health and beauty exist among individuals. Nonetheless, various factors contribute to facial skin issues, including exposure to free radicals during outdoor activities. Recently, sheet masks have gained popularity as a hygiene and efficient method for facial care. Therefore, this study aims to incorporate matoa fruit peel as an active component in sheet masks. These masks will be formulated and subjected to tests measuring antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method, as well as antibacterial activity through the disc diffusion method to assess inhibition zones against Propionibacterium acnes bacteria. The assessment encompasses organoleptic tests, pH measurement, homogeneity, and stability. Findings from the study reveal that the sheet mask formulation is slightly viscous, possessing a distinctive odor and a light brown color. The pH of the sheet mask formulation ranges between 5.3 and 5.15. The formulation exhibits homogeneity at both 3°C and room temperature. Stability is maintained with no observable changes in color, odor, or consistency at 3°C and room temperature. Additionally, there were no reported irritations by the 12 volunteers during the skin irritation test. Antioxidant testing demonstrates high activity, with inhibition percentages of 74.47% (1:1) and 42.68% (0.5:1). In contrast, antibacterial testing indicates moderate efficacy, with an inhibition zone of 5.8667 mm. The research affirms that the matoa fruit peel extract formulated in the sheet mask exhibits both antioxidant and antibacterial    properties suitable for addressing acne in facial skincare.